Intraoral Hemangioma: An overview of the clinical entity - Khyati Trivedi; Amit Soni; Rufus Meshack; Rakhi Satynarayan Kulthya (Wolters Kluwer Medknow Publications, 2015)
Hemangiomas are common tumors characterized microscopically by proliferation of blood vessels. The congenital hemangioma is often present at birth and may become more apparent throughout life. They are probably developmental rather than neoplastic in origin. Despite their benign origin and behavior, hemangiomas in the oral cavity are always of clinical importance to the dental profession and require appropriate clinical management. Surgery and other treatment modalities are not always satisfactory and have a higher morbidity, recurrence, and complication rate. This case report presents a case of hemangioma of mandibular left lower region in 47-year-old female and its treatment using sclerosing agent.